2013
DOI: 10.1371/journal.pone.0082957
|View full text |Cite
|
Sign up to set email alerts
|

ERK/PP1a/PLB/SERCA2a and JNK Pathways Are Involved in Luteolin-Mediated Protection of Rat Hearts and Cardiomyocytes following Ischemia/Reperfusion

Abstract: Luteolin has long been used in traditional Chinese medicine for treatment of various diseases. Recent studies have suggested that administration of luteolin yields cardioprotective effects during ischemia/reperfusion (I/R) in rats. However, the precise mechanisms of this action remain unclear. The aim of this study is to confirm that luteolin-mediated extracellular signal regulated kinase (ERK1/2) and c-Jun N-terminal kinase (JNK) pathways are responsible for their cardioprotective effects during I/R. Wistar r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 39 publications
2
60
3
Order By: Relevance
“…MAPK compounds, including ERK, stress-activated protein kinases/c-Jun NH 2 -terminal kinases and p38 MAPKs have been implicated in inflammatory signaling mechanisms in I/R injury (30,31). Additionally, ERK signaling serves a crucial function in I/R-induced cell apoptosis (32,33). Ban et al (34) reported that the inhibition of ERK signaling worsened intestinal I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…MAPK compounds, including ERK, stress-activated protein kinases/c-Jun NH 2 -terminal kinases and p38 MAPKs have been implicated in inflammatory signaling mechanisms in I/R injury (30,31). Additionally, ERK signaling serves a crucial function in I/R-induced cell apoptosis (32,33). Ban et al (34) reported that the inhibition of ERK signaling worsened intestinal I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…Single ventricular myocytes were obtained from the isolated rat hearts using type II collagenase (Gibco, Grand Island, NY, USA) as previously described [14, 23-25]. The cells were suspended 3 times with Krebs-bicarbonate solution (pH 7.2) containing (mM) 85 KCl, 15 NaCl, 5 MgSO 4 , 30 KH 2 PO 4 , 5 sodium pyruvate, 5 creatine, 20 taurine, 2 L-glutamic acid, 20 HEPES, 20 glucose, 0.2 CaCl2 and 0.5 EGTA, and was bubbled with 100% O 2 at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Global I/R of the rat hearts was performed ex vivo according to our previous procedure [14]. Sodium heparin (1000 U/kg) and sodium pentobarbital (150 mg/kg) was administered to the experiment animals, then the rat hearts were excised and perfused, by Langendorff, with Krebs-Henseleit (KH) buffer solution containing (mM) 120 NaCl, 4.7 KCl, 1.2 KH 2 PO 4 , 1.2 MgSO 4 , 25 NaHCO 3 , 11 glucose and 1.25 CaCl 2, which was bubbled with 95% O 2 and 5% CO 2 at 37°C to maintain a pH of 7.4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNAs (miRNAs) are noncoding RNA involved in the post-transcriptional regulation of protein expression, it has been demonstrated that miRNAs may contribute to classical IPC cardioprotection (40). According to the results of recent studies (1,(41)(42)(43), Lut is an interesting agent, it not only can play a role in multi-signalling pathway, but also can modulate miRNAs in the cardioprotection. The role of Lut in modulating miR-146b-5p and SECA2a/BAG1 against myocardial IRI is processing in our study.…”
mentioning
confidence: 99%